Dose and Time Dependencies in Stress Pathway Responses during Chemical Exposure: Novel Insights from Gene Regulatory Networks - Souza, Terezinha M.; Kleinjans, Jos C. S.; Jennen, Danyel G. J. (Frontiers in Genetics, 2017)
Perturbation of biological networks is often observed during exposure to xenobiotics, and the identification of disturbed processes, their dynamic traits and dose-response relationships are some of the current challenges for elucidating the mechanisms determining adverse outcomes. In this scenario, reverse engineering of gene regulatory networks (GRNs) from expression data may provide a system-level snapshot embedded within accurate molecular events. Here, we investigate the composition of GRNs inferred from groups of chemicals with two distinct outcomes, namely carcinogenicity (azathioprine and cyclophosphamide) and drug-induced liver injury (DILI; diclofenac, nitrofurantoin and propylthiouracil), and a non-carcinogenic/non-DILI group (aspirin, diazepam and omeprazole). For this, we analyzed publicly available exposed in vitro human data, taking into account dose and time dependencies. DTNI (Dose and Time Network Identification) was applied to gene sets from exposed primary human hepatocytes using four stress pathways, namely endoplasmic reticulum (ER), NF-B, NRF2 and TP53. Inferred GRNs suggested case specificity, varying in interactions, starting nodes and target genes across groups. DILI and carcinogenic compounds were shown to directly affect all pathway-based GRNs, while non-DILI/non-carcinogenic chemicals only affected NF-B. NF-B-based GRNs clearly illustrated group-specific disturbances, with the cancer-related casein kinase CSNK2A1 being a target gene only in the carcinogenic group, and opposite regulation of NF-B subunits being observed in DILI and non-DILI/non-carcinogenic groups. Target genes in NRF2-based GRNs shared by DILI and carcinogenic compounds suggested markers of hepatotoxicity. Finally, we indicate several of these group-specific interactions as potentially novel. In summary, our reversed-engineered GRNs are capable of revealing dose-dependent, chemical-specific mechanisms of action in stress-related biological networks.